2017
DOI: 10.11648/j.jher.20170301.12
|View full text |Cite
|
Sign up to set email alerts
|

Perception of and Adaptive Capacities to Climate Change Adaptation Strategies and Their Effects on Rice Production: A Case of Pabna District, Bangladesh

Abstract: Abstract:Bangladesh is one of the most sensitive hotspot for climate change and climate-related extreme events which significantly affect agricultural production. As a result farmers' try to minimize the adverse affects by various adaptation strategies. The aim of the study is thus, perception of and adaption capacities to climate change adaption strategies and their effects on rice production in a moderate level of drought severity and groundwater depletion but greater cropping diversity area (Pabna District)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
4
10
0
Order By: Relevance
“…In addition, the analysis using binary logistic regression highlighted age of paddy farmers, monthly income of paddy farmers, and the district in which paddy farmers reside as the factors that associated with the level of adaptive capacity significantly. These findings are in line with the previous studies ( [15], [21], [25]). Furthermore, the findings could assist KADA and agricultural authorities in Kelantan to take appropriate measures in ensuring paddy farmers in Kelantan to be highly adaptive towards the changes in climate.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, the analysis using binary logistic regression highlighted age of paddy farmers, monthly income of paddy farmers, and the district in which paddy farmers reside as the factors that associated with the level of adaptive capacity significantly. These findings are in line with the previous studies ( [15], [21], [25]). Furthermore, the findings could assist KADA and agricultural authorities in Kelantan to take appropriate measures in ensuring paddy farmers in Kelantan to be highly adaptive towards the changes in climate.…”
Section: Resultssupporting
confidence: 94%
“…The final step involved classifying the sores into three different levels of adaptive capacity which are low, moderate, and high. Table 2 shows the three categories of adaptive capacity which are based on the range levels referred from the previous study [21].…”
Section: Classification Of Adaptive Capacity's Scoresmentioning
confidence: 99%
“…Farmers who can access more credit adopt a more sustainable farming culture than those who access less. Sarker et al (2013), Eyasmin et al (2017), Linh et al (2019), and Adeleye et al ( 2020) also found a positive and statistically significant relationship between accessing credit and sustainable agricultural production. In all three dimensions of economic, environmental, and social sustainability, the relation between extended contacts and production sustainability is highly significant at a 1% significance level, though receiving higher extension services will result in higher social and environmental sustainability than economic sustainability as extension contacts become environmentally viable such as soil conservation, minimizing pesticides use, and organic farming.…”
Section: Sustainability Of Socio-economic Characteristicsmentioning
confidence: 94%
“…Figure 1 shows the study area, in which 79.85% of the people in the survey have their livelihood on agriculture. Moreover, Ishwardi Upazila and Lalpur Upazila reach their peak vulnerability from the intensity and frequent drought (Alauddin and Sarker, 2014;Eyasmin et al, 2017). The survey questionnaire included the 14 adaptation strategies such as irrigation, chemical fertilizer application, organic manure application, restructure cash flow and debt, crop rotation, offfarm activities, diseases tolerant varieties, changing planting dates, drought tolerance rice varieties, and crop diversification, which were identified in different studies in the drought-prone area (Ghosh et al, 2016;Eyasmin et al, 2017;Kabir et al, 2017).…”
Section: Research Design and Methodology Study Area Description Of Variables Summary Statisticsmentioning
confidence: 99%
See 1 more Smart Citation